Critical Review: Emotion: A Religio-Psychological Explanation Of Human Emotions In The Qur’an From Darwis Hude - Amiruddin Nahrawi (Psikis : Jurnal Psikologi Islami, 2020)
The dissertation written by M. Darwis Hude entitled "Human Emotions in the Qur’an: Study through a Psychological Approach" is an effort to explore and formulate the concept of emotions that exist in the Qur’an. This study aims to conduct a critical review of the work of Darwis Hude in order to develop a scientific concept, particularly on the study of emotions in the Qur’an. This research is a qualitative research with a critical review study method which aims to evaluate, review, interpret and analyze the contents of an article or book by considering the strengths and the weaknesses of a work. The results of the study found that Hude's dissertation which is explicitly psychological and theological in nature becomes the spirit of studying the essence and noble values ​​of the Qur’an. In terms of the preparation and writing of the book, it is quite interesting to study but it needs a comprehensive development with other branches of science. In addition, Hude in explaining verses related to emotions tends not to use the interpretation or views of the cleric. In terms of number of pages, there are several chapters that are less efficient but the last two chapters are quite ideal for important discussions. Then in terms of references Hude has balanced using relevant references, including books. It's just that the views of the clerics or their interpretations are less emphasized.